Luteoloside Inhibits IL-1β-Induced Apoptosis and Catabolism in Nucleus Pulposus Cells and Ameliorates Intervertebral Disk Degeneration - Lin, Jialiang; Chen, Jiaoxiang; Zhang, Zengjie; Xu, Tianzhen; Shao, Zhenxuan; Wang, Xiaobin; Ding, Yuanzhe; Tian, Naifeng; Jin, Haiming; Sheng, Sunren; Gao, Weiyang; Lin, Yan; et al. (Frontiers in Pharmacology, 2019)
Intervertebral disk degeneration (IDD) is the major cause of low back pain (LBP), which affects 80% of the world’s population. Interleukin 1 beta (IL-1β) is a major inflammatory factor that accelerates disk degeneration, and IL-1β levels increase in degenerative disks. It has recently been reported that luteoloside—a type of flavonoid glycoside—has anti-inflammatory properties. In the present study, we investigated the protective potential of luteoloside in IDD. We found that luteoloside maintains cell morphology and inhibits apoptosis (indicated by the reduced expression of cleaved caspase 3) in IL-1β-treated nucleus pulposus (NP) cells. It also suppresses inflammatory mediators—nitric oxide (NO), prostaglandin E2 (PGE2), tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), cyclooxygenase 2 (COX-2), and inducible nitric oxide synthase (iNOS)—in IL-1β-treated NP cells. Furthermore, we found increased collagen II and aggrecan expression and reduced MMP13 and ADAMTS5 expression in luteoloside-treated NP cells in the presence of IL-1β. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is involved in apoptosis, inflammation, and extracellular matrix (ECM) homeostasis. Mechanistic studies revealed that the NF-κB signaling pathway is inhibited by luteoloside, and Nrf2 is involved in the regulation of luteoloside in NF-κB signaling because Nrf2 knockdown reduced the suppressive effect of luteoloside on NF-κB signaling. We also established a puncture-induced rat IDD model and demonstrated that the persistent intraperitoneal injection of luteoloside ameliorates the progression of IDD. In conclusion, we demonstrated that luteoloside activates the Nrf2/HO-1 signaling axis and is a potential therapeutic medicine for IDD.